2016
DOI: 10.1002/chem.201603956
|View full text |Cite
|
Sign up to set email alerts
|

Mechanistic Study of the Stereoselective Hydroxylation of [2‐2H1,3‐2H1]Butanes Catalyzed by Cytochrome P450 BM3 Variants

Abstract: Engineered bacterial cytochrome P450s are noted for their ability in the oxidation of inert small alkanes. Cytochrome P450 BM3 L188P A328F (BM3 PF) and A74E L188P A328F (BM3 EPF) variants are able to efficiently oxidize n-butane to 2-butanol. Esterification of the 2-butanol derived from this reaction mediated by the aforementioned two mutants gives diastereomeric excesses (de) of -56±1 and -52±1 %, respectively, with the preference for the oxidation occurring at the C-H bond. When tailored (2R,3R)- and (2S,3S)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 76 publications
(81 reference statements)
1
2
0
Order By: Relevance
“…The EPR spectrum of copper oxide nanoparticles at 298 K indicated an isotropic signal, reminiscent of a previous study of pMMO with trinuclear copper cluster feature (Nguyen et al, 1994), which was significantly broadened and presented relatively poor signal-to-noise ratio than the one at 77 K ( Figure 3B) (Wanna et al, 2019b). The result here reveals substantial dynamic motions around the metal centers, which are behaving like metal active sites in the metallo-monooxygenases (Chen et al, 2014;Wang et al, 2017;Yang et al, 2017). In addition, the corresponding EXAFS data fittings (k 3 -weighted) using two structural models of copper oxide and trinuclear copper cluster model (Cu 2.8 O 4.6 ), respectively, can both give reasonable fits of R fit = 0.027 and 0.15%, respectively (Wanna et al, 2019b), which indicated that a trinuclear copper cluster feature is manifested from the obtained oxide materials (Figure 3).…”
Section: Highly Selective Oxidation Of Benzene To P-benzoquinone (P-bsupporting
confidence: 80%
“…The EPR spectrum of copper oxide nanoparticles at 298 K indicated an isotropic signal, reminiscent of a previous study of pMMO with trinuclear copper cluster feature (Nguyen et al, 1994), which was significantly broadened and presented relatively poor signal-to-noise ratio than the one at 77 K ( Figure 3B) (Wanna et al, 2019b). The result here reveals substantial dynamic motions around the metal centers, which are behaving like metal active sites in the metallo-monooxygenases (Chen et al, 2014;Wang et al, 2017;Yang et al, 2017). In addition, the corresponding EXAFS data fittings (k 3 -weighted) using two structural models of copper oxide and trinuclear copper cluster model (Cu 2.8 O 4.6 ), respectively, can both give reasonable fits of R fit = 0.027 and 0.15%, respectively (Wanna et al, 2019b), which indicated that a trinuclear copper cluster feature is manifested from the obtained oxide materials (Figure 3).…”
Section: Highly Selective Oxidation Of Benzene To P-benzoquinone (P-bsupporting
confidence: 80%
“…All positions of the P450 BM3 heme domain that have been mutated and show improvement toward small alkyl hydroxylation are shown (yellow spheres). Mutated positions in the heme domain (residues 1–471) and in the reductase domain (472–1049) are listed, with refs: 4 (), 26 ( , , , , ), 47 ( , , , , , , , , , , , , , , , , , , , , , ), 51 ( , , , , , , , , , , ), 52 ( , , , ), 64 ( , ), 70 (), 72 (), 74 ( , , , , , , , , , , , , , , ), 75 ( , , , , , , ), 78 ( , , , , …”
Section: P450 Bm3 Variants Catalyzing Small Alkyl Hydroxylationmentioning
confidence: 99%
“…Synthetic metalloporphyrins and other macrocycles (tetrapyrrolic or not) were described as excellent cytochrome P450 biomimetic catalysts to promote a selective and efficient family of reactions, such as olefin epoxidation and alkane (linear and cyclic) hydroxylation [ 27 , 28 , 29 , 30 , 31 , 32 ]. Despite the many reports, there are few examples of the design and preparation of efficient catalytic systems able to promote sequential one-pot reactions involving catalyst species based on metalloporphyrins.…”
Section: Introductionmentioning
confidence: 99%